PENGARUH PROMOSI, KUALITAS PRODUK DAN KEPERCAYAAN TERHADAP MINAT BELANJA PADA ONLINE SHOP YANG MENGGUNAKAN INSTAGRAM DI KOTA DENPASAR - Made Friska Walesasi; Ni Putu Nita Anggraini; Pande Ketut Ribek (Program Studi Manajemen Fakultas Ekonomi dan Bisnis UNMAS, 2022)
One line of business that has high competition on Instagram is an online shop. According to data from kompas.com, no less than 45 million active monthly Instagram users come from Indonesia. This study aims to determine whether promotion, product quality and online shop trust on Instagram affect the shopping interest of people in the city of Denpasar. Collecting data using a 5-point Likert scale questionnaire. The number of samples used was 105 people using the proportional sampling method. Data analysis technique using multiple linear regression test. The results of the study show that promotion has a positive and significant effect on shopping interest. Product quality has a positive and significant effect on shopping interest. Trust has a positive and significant effect on shopping interest, which means that the higher the trust, the higher the shopping interest. It is recommended to increase the frequency of promotions on Instagram media, pay attention to the suitability of the specifications of the products being sold with market segments, and it is suggested that online stores in promoting the goods being sold provide narratives as they are, so that there are no differences in buyer expectations.